2023
DOI: 10.3934/gf.2023001
|View full text |Cite
|
Sign up to set email alerts
|

Green finance engagement: An empirical study of listed companies on Chinese main board

Abstract: <abstract> <p>Using textual analysis, this paper divides green finance into green initiatives and green business activities. The former discusses whether environmental initiatives shall be signed, while the latter explores whether various emerging green commodities and services are provided. This paper investigates the influence of corporate size, the degree of internationalization, profits and competitiveness on the engagement degree of green finance, according to data collected from 410 Chinese l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Enterprises’ contributions to environmental protection play a vital role in corporate social responsibility and positively impact corporate reputation and financial performance [ 46 ]. Additionally, Huang et al (2023) explore the effects of corporate size, degree of internationalization, profits, and competitiveness on the degree of engagement in green finance and find that corporate size is positively related to the degree of engagement in green finance [ 47 ]. Huang et al (2019) have demonstrated the positive role of green loans and government subsidies in promoting corporate green innovation [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Enterprises’ contributions to environmental protection play a vital role in corporate social responsibility and positively impact corporate reputation and financial performance [ 46 ]. Additionally, Huang et al (2023) explore the effects of corporate size, degree of internationalization, profits, and competitiveness on the degree of engagement in green finance and find that corporate size is positively related to the degree of engagement in green finance [ 47 ]. Huang et al (2019) have demonstrated the positive role of green loans and government subsidies in promoting corporate green innovation [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Topik utama yang saat ini kerap kali dijadikan permasalahan pada sebuah perusahaan yakni tentang masalah lingkungan. Masalah lingkungan seperti perubahan iklim, hilangnya keanekaragaman hayati dan kerusakan lahan menarik perhatian dunia (Huang et al, 2023).…”
Section: Pendahuluanunclassified